Vascular Changes in the Retina and Choroid of Patients With EPAS1 Gain-of-Function Mutation Syndrome - Dmitriev, Pauline M. (JAMA Ophthalmol, 2020)
IMPORTANCE: Patients with the EPAS1 gain-of-function mutation syndrome (or Pacak-Zhuang syndrome) present with multiple paragangliomas or pheochromocytomas, duodenal somatostatinoma, polycythemia, headaches, and sometimes diminished visual acuity at an early age. The characteristic phenotype and known genetic cause of the syndrome provide an opportunity to study the role of hypoxia-inducible factor 2α (HIF-2α) in oxygen sensing, development in regions of physiologic hypoxia, and other pathological processes. OBJECTIVES: To describe the ocular lesions in EPAS1 gain-of-function mutation syndrome and to establish whether early-onset diminished visual acuity is developmental or associated with long-term physiologic sequelae of the syndrome. DESIGN, SETTING, AND PARTICIPANTS: This clinical case series with a transgenic murine model study was conducted from July 2013 to June 2019. Participants were 3 patients referred by their primary care physicians to the National Institutes of Health for evaluation of recurrent and metastatic paragangliomas or pheochromocytomas accompanied by polycythemia. The syndrome and somatic mosaicism in patients were confirmed by the identification of gain-of-function mutations in the EPAS1 gene in resected tumors and other tissues. MAIN OUTCOMES AND MEASURES: Ocular findings in patients with EPAS1 gain-of-function mutation syndrome. RESULTS: A total of 3 patients (mean [SD] age, 29 [6.2] years) with confirmed ocular abnormalities were included in the study. Increased contrast accumulation at the posterior aspect of the globe was seen bilaterally on magnetic resonance imaging scans in all patients. Ophthalmoscopy images demonstrated fibrosis overlying the optic disc, tortuous and dilated retinal vessels, and retinal pigment epithelium changes. Optic disc edema and retinal exudates were also seen. Fluorescein angiography images showed leakage of dye from postcapillary venules surrounding the optic disc and highlighted aberrant retinal vascular patterns. Enhanced-depth imaging optical coherence tomography images showed substantial thickening of the choroid and dilation of choroidal vessels. The ocular features of the syndrome were confirmed with a transgenic model of mice with gain-of-function Epas1(A529V) mutation. CONCLUSIONS AND RELEVANCE: In this case series, HIF-2α and hypoxia signaling was found to have a role in vessel development within the choroid and retina, indicating that the marked permanent choroidal thickening and tortuous and dilated veins seen in the choroid and retina in patients with EPAS1 gain-of-function mutation syndrome were suggestive of the persistence of venous elements within the developing mesenchyme. These findings may explain other eye and vascular abnormalities whose pathogenesis remains unclear.